Concomitant abuse of anabolic androgenic steroids and human chorionic gonadotrophin impairs spermatogenesis in power athletes - Karila, T.; Hovatta, O.; Seppälä, T. (International Journal of Sports Medicine, 2004)
Abuse of anabolic androgenic steroids (AASs) may be an aetiological factor in male infertility among recreational power athletes. They try to avoid AAS-induced deterioration in spermatogenesis by combining doses of human chorionic gonadotrophin (HCG) and/or antiestrogens with their AAS abuse. Eighteen healthy male power athletes using massive doses of AASs were recruited for the study. Semen samples were collected during AAS abuse and 1.5 and 6 months after cessation of the abuse. They were also asked about their reproductive activity six years after the study. At the end of the AAS cycle, the sperm count was 33 ± 49 × 106 /ml (mean ± SD), and only one subject had azoospermia. At 1.5 months after cessation of the AAS cycles, the mean sperm concentration was 30 ± 42 × 106 /ml, and after six months 77 ± 70 × 106 /ml. There were significant differences between the sample drawn six months after cessation of AAS abuse and both samples drawn during and 1.5 months after the abuse (p = 0.05, repeated measures of ANOVA). There was a significant positive correlation between HCG dose during the cycle and the relative amount of morphologically abnormal spermatozoa (r = 0.60, p < 0.01). The concomitant abuse of HCG and supraphysiological AAS dose cause transient impairment on semen quality in males, although spermatogenesis is maintained with this regimen despite prolonged abuse of massive doses of AAS.